Writing the Sacred from Within in Richard Burton’s A Personal Narrative of a Pilgrimage to El-Medinah and Meccah - Usmani, Raeesabegam; Mehta, Kunjal Malvik (Muslim English Literature, 2025)
The West has shown the utmost curiosity for the Middle East's culture, tradition, society, and the Hajj pilgrimage. This region was considered the least explored on the world map until the nineteenth century. Over the decades, a handful of adventurers and explorers have undertaken various perilous journeys to find answers and satisfy the inquisitiveness of a larger, knowledge-thirsty populace. Travel writing, Hajj pilgrimage travel writing, can still not be considered an established area of study. This paper aims to highlight the pilgrimage travelogues of the nineteenth century by drawing scholarly attention to the genre of Hajj pilgrimage travel writing, its significance, and the need for more academic attention. The paper critically analyses Sir Richard Burton’s travelogue A Personal Narrative of a Pilgrimage to El-Medinah and Meccah (1855), which recounts his journey to the cities of Mecca and Medina and the Hajj pilgrimage from the nineteenth century. He undertook the Hajj pilgrimage in disguise as a Muslim pilgrim, a journey fraught with numerous challenges and dangers. The paper primarily critically analyses the motivations of this so-called pilgrim from the West, his reflections on the Oriental society, culture, religious sites, and life in the Middle East, along with the challenges he faced during this perilous journey. It also critically examines how he attempted to reconcile his Englishness with an adopted Muslim guise or identity and its impact on the narration and description in the travelogue.